2017
DOI: 10.1080/21513732.2016.1275811
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs among ecosystem services under different pinion harvesting intensities in Brazilian Araucaria Forests

Abstract: Assessing the consequences of human exploitation at different intensities on ecosystem services is important in the Brazilian Araucaria Forest biome, because it has been drastically reduced, mainly due to the exploitation of Araucaria angustifolia (Bertol.) Kuntze for wood. The inclusion of A. angustifolia on the list of Brazilian endangered plant species places the harvesting of Araucaria nuts as the most important provisioning service in this type of ecosystem. The aim of this study was to determine the trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…In this context, source of income from pinhão is the main incentive for the preservation of Araucaria—and its biome (Hanazaki, Zank, Fonseca‐Kruel, & Schmidt, 2018), since it is now considered an endangered species and shows important impact for the regional development of the Southern states of Brazil (Fichino, Pivello, & Santos, 2017; Peralta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, source of income from pinhão is the main incentive for the preservation of Araucaria—and its biome (Hanazaki, Zank, Fonseca‐Kruel, & Schmidt, 2018), since it is now considered an endangered species and shows important impact for the regional development of the Southern states of Brazil (Fichino, Pivello, & Santos, 2017; Peralta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For the Brazilian case, we built two equations to express the monitoring methods for the service of provision of Brazil nuts (Table ). Similar and more detailed analysis was done by Fichino et al () for the Araucaria nut from Southern Brazil. Using flora inventories required by government as part of the baseline necessary for the mining and restoration approval process, we found that there are on average five trees per hectare in premined forest.…”
Section: Resultsmentioning
confidence: 59%
“…Araucaria angustifolia is a tree from southern Brazil [18] . It is an endangered species, and there are legal restrictions concerning the use of its wood; therefore, incentives are given to the commercialization of its seed, the pine nut [19] . Pine nut is a nutritious food, containing mainly starch and low amounts of sugars and lipids in its composition [20] .…”
Section: Introductionmentioning
confidence: 99%